A processing method for improving the anti-pilling level of aramid viscose blended fabric
Patent Information
- Application Number
- CN202611175832.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0010]针对芳纶粘胶织物抗起球等级低、耐久性差及整理后手感硬、透气性差的技术问题,本发明提供一种提升芳纶粘胶混纺织物抗起毛起球级别的加工方法,通过环氧硅烷偶联剂协同烧碱进行表面活化处理,增加纤维表面极性与反应活性;再采用柔性丙烯酸酯乳液、2D树脂与环氧交联剂组成的复配整理液浸轧,于110~120℃低温焙烘固化
1、本发明采用环氧型硅烷偶联剂协同烧碱对织物进行表面活化处理,解决了芳纶表面惰性强、树脂附着力差的问题;配合柔性丙烯酸酯乳液、2D树脂与交联剂组成的复配整理液浸轧,并于110~120℃低温焙烘固化。该方法使织物抗起毛起球等级由2~3级提升至4~5级,10次水洗后仍维持4级以上,耐洗性优异;同时,柔性丙烯酸酯乳液与柔软剂协同成膜,避免手感僵硬,整理后织物强力保持率≥95%、透气性基本无损失,实现了抗起球性能与服用品质的兼顾。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile finishing technology, specifically to a processing method for improving the pilling resistance of aramid-viscose blended fabrics. Background Technology
[0002] Aramid fibers possess excellent properties such as ultra-high strength, high modulus, high temperature resistance, flame retardancy, and chemical corrosion resistance, making them a high-end protective textile material. Viscose fibers offer advantages such as moisture absorption and breathability, soft hand feel, good drape, and comfortable wear. Aramid and viscose blended fabrics can balance protective performance with wearing comfort, and are widely used in firefighting gear, special protective clothing, functional home textiles, and industrial protective fabrics.
[0003] However, aramid and viscose fibers have vastly different physical and chemical properties, resulting in severe pilling and fuzzing defects in blended fabrics. Aramid fibers have a smooth surface, low coefficient of friction, poor fiber cohesion, high rigidity, and are difficult to break, making them prone to acting as rigid ball nuclei during friction. Viscose fibers, on the other hand, have low wet strength, high short fiber content, and poor abrasion resistance, making them extremely susceptible to pulling, curling, breaking, and detaching after being subjected to external friction, bending, or washing. Under the synergistic effect of the two fibers, loose viscose short fibers entangle with rigid aramid fibers to form stubborn pills. Conventional aramid-viscose fabrics only achieve a pilling resistance rating of 2-3, exhibiting excessive fuzz and poor washability, severely restricting the high-end application and service life of the products.
[0004] Currently, various treatment methods have been disclosed in existing technologies to address the problem of pilling and fuzzing in textile fabrics. For example, patent CN109610173A discloses a finishing liquid and method for textiles with durable anti-wrinkle, moisture-wicking, quick-drying, and anti-pilling properties. It uses an etherified modified dihydroxymethyl dihydroxyvinyl urea resin and a cationic end-capped polyurethane resin for padding finishing. However, the fiber system of this technology is conventional fabrics such as pure cotton, polyester-cotton, and nylon-cotton blends, not aramid-viscose blends, and its baking temperature is as high as 150-170℃.
[0005] Patent CN102433746B discloses a method for improving the anti-pilling performance of acrylic fabrics. It uses a strong alkali to modify acrylic fibers and then finishes them with a resin finishing agent. The alkali activation mechanism is based on the specific hydrolysis reaction of cyano groups (-CN) on the acrylic molecular chain under alkaline conditions. Aramid and viscose do not have such hydrolyzable side groups and cannot be directly applied to aramid-viscose blended systems.
[0006] The patent with publication number CN121538837A discloses a finishing method for improving the anti-pilling and anti-fuzzing properties of cotton fabrics at room temperature. It uses an amphoteric-nonionic composite surfactant and hydroxypropyltrimethylammonium chloride chitosan (HPTCC) to prepare a treatment solution. However, this technology is only applicable to pure cotton fabrics, and its acid hydrolysis mechanism is based on the selective hydrolysis of the amorphous region of cotton fiber cellulose.
[0007] Patent CN122257234A discloses a method and application for improving the pilling and fuzzing of polyester-modal blended fabrics. It adopts an integrated process of desizing, pre-shrinking, dry setting, singeing with a flame cut, and finishing with a polymer resin containing surfactant. However, the fiber system of this technology is a polyester-modal blended fabric. The surface chemical properties and pilling mechanism of polyester and modal are quite different from those of aramid viscose fibers. For aramid viscose fabrics, singeing can only remove long hairs on the surface but cannot fix the free short fibers inside the yarn, making it difficult to achieve a durable anti-pilling effect.
[0008] However, existing anti-pilling finishing technologies generally have the following shortcomings: First, singeing can only remove long surface hairs and cannot fix the free short fibers inside the yarn, resulting in poor durable anti-pilling effect; second, high-temperature resin finishing can easily lead to stiff fabric feel, a significant decrease in breathability and moisture permeability, and loss of fabric comfort; third, existing fabric anti-pilling treatment methods are mostly for polyester-molybdenum blended fabrics, cotton fabrics, and acrylic fabrics, and there is still a gap in the industry for a special finishing process for aramid-viscose blended fabrics that takes into account high anti-pilling level, soft feel, breathability and shape retention, and washability.
[0009] Therefore, there is an urgent need to develop a special finishing process for aramid viscose fabrics that can take into account high anti-pilling rating, soft hand feel, breathability and shape retention, and water resistance. Summary of the Invention
[0010] To address the technical problems of low pilling resistance, poor durability, and stiff hand feel and poor breathability after finishing aramid viscose fabrics, this invention provides a processing method to improve the pilling resistance of aramid viscose blended fabrics. The method involves surface activation treatment using an epoxy silane coupling agent in conjunction with caustic soda to increase fiber surface polarity and reactivity; followed by padding with a compound finishing solution consisting of a flexible acrylate emulsion, 2D resin, and epoxy crosslinking agent, and curing at a low temperature of 110–120°C. The finished fabric achieves a pilling resistance grade of 4–4.5, maintaining a grade of 4 or higher after 10 washes, while retaining a soft hand feel, undamaged breathability, and a strength retention rate of no less than 95%.
[0011] The technical solution of this invention is as follows: In a first aspect, the present invention provides a processing method for improving the pilling resistance of aramid-viscose blended fabrics, comprising the following steps: S1. The aramid-viscose blended fabric is subjected to desizing, scouring and setting treatments in sequence. S2. Impregnate the fabric with the pretreatment solution obtained in step S1; S3. Apply the fabric padding finishing solution obtained in step S2; S4. The fabric obtained in step S3 is pre-dried and then baked at low temperature in sequence. S5. Wash, dry and set the fabric obtained in step S4 to obtain the finished product.
[0012] Furthermore, in step S1, the basis weight of the aramid-viscose blended fabric is 180–260 g / m². 2 The mass ratio of aramid fiber to adhesive fiber in the aramid-viscose blended fabric is 30:70 to 70:30.
[0013] Furthermore, in step S2, the pretreatment solution includes an epoxy silane coupling agent and caustic soda, wherein the concentration of the epoxy silane coupling agent is 5–15 g / L, and the concentration of the caustic soda is 5–15 g / L. Through the synergistic effect of the epoxy silane coupling agent and caustic soda, on the one hand, a mild etching process is applied to the surface of the viscose fiber to increase surface roughness; on the other hand, epoxy active groups are introduced onto the surface of the aramid and viscose fibers, significantly improving the surface polarity and reactivity of the fibers. This greatly enhances the adhesion and bonding strength between the resin in the subsequent finishing solution and the fiber, solving the problem of resin easy detachment and poor durability caused by the inertness of the aramid surface.
[0014] Furthermore, in step S3, the finishing liquid comprises the following components in mass concentrations: flexible acrylate emulsion 15~25g / L, 2D resin 75~90g / L, crosslinking agent 15~22g / L, refining agent 5~18g / L, and softener 40~50g / L.
[0015] Furthermore, the flexible acrylic emulsion is an anionic acrylic emulsion, model Appretan® N96101 liq. Anionic acrylic emulsions form uniform, soft, and non-stiff films, creating an ultra-thin, flexible protective film on the fiber surface to bind free short fibers without clogging fabric pores, thus ensuring breathability.
[0016] Furthermore, the main component of the 2D resin is a resin condensate with a polyhydroxymethyl structure, model PM-300; the crosslinking agent is model crosslinking agent S; the scouring agent is model scouring HF-JL5; and the softener is model HF-08R.
[0017] Furthermore, the main component of the softener is amino silicone oil.
[0018] Furthermore, the rolling process employs a one-dip-one-roll method, with a roll residue rate of 65% to 75%.
[0019] Furthermore, in step S4, the pre-baking temperature is 80–90°C, and the pre-baking time is 2–4 minutes; the low-temperature baking temperature is 110–120°C, and the low-temperature baking time is 1.5–3 minutes. Low-temperature baking can achieve mild cross-linking and cure the resin system, while avoiding high-temperature damage to the strength and feel of the viscose fibers.
[0020] Furthermore, in step S5, the water washing is done with warm water at 40-50℃, and the drying temperature is 95-105℃.
[0021] Furthermore, in step S5, the anti-pilling grade of the finished aramid viscose fabric reaches level 4-5, and after 10 washes, the anti-pilling grade is not lower than level 4.
[0022] The beneficial effects of this invention are as follows: 1. This invention employs an epoxy-type silane coupling agent in conjunction with caustic soda to perform surface activation treatment on fabrics, solving the problems of strong surface inertness and poor resin adhesion of aramid fibers. It then combines this with a compound finishing solution consisting of a flexible acrylic emulsion, 2D resin, and a crosslinking agent for padding, followed by low-temperature baking and curing at 110–120°C. This method improves the fabric's anti-pilling grade from 2–3 to 4–5, maintaining a grade of 4 or higher after 10 washes, demonstrating excellent wash resistance. Simultaneously, the flexible acrylic emulsion and softener synergistically form a film, preventing a stiff hand feel. The finished fabric retains ≥95% of its strength and exhibits virtually no loss of breathability, achieving a balance between anti-pilling performance and garment quality.
[0023] 2. The process of this invention is simple, the conditions are mild, the energy consumption is low, there are no harmful additives, it is green and environmentally friendly, and it is suitable for large-scale industrial continuous production, with good prospects for industrial promotion and application. Detailed Implementation
[0024] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions in the embodiments of this invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this invention.
[0025] 1. Unless otherwise specified, the raw materials and reagents used in the embodiments and comparative examples of this invention are all commercially available industrial-grade or analytical-grade products, which can be obtained through commercial channels; the specifications and sources of the main raw materials are as follows: Flexible acrylic emulsion: Appretan® N96101 liq, purchased from Anggao Chemical Co., Ltd.; 2D resin: The main component is a resin condensate with a polyhydroxymethyl structure; pH value (1% aqueous solution) 3.5-5.5; Model PM-300, purchased from Liansheng Chemical. Crosslinking agent: Model S, purchased from Liansheng Chemical; Refining agent: Model HF-JL5, purchased from Huafang Co., Ltd.; Softener: HF-08R type, purchased from Huafang Co., Ltd.
[0026] 2. Unless otherwise specified, the instruments and equipment used in the embodiments and comparative examples of this invention are all conventional experimental equipment in the field.
[0027] I. Implementation Examples Example 1 A processing method for improving the pilling resistance of aramid-viscose blended fabrics includes the following steps: S1. Fabric pretreatment: Select an aramid / viscose blended fabric with a weight of 220g / m². 2 The fabric is then desized, boiled, and set in sequence to remove impurities and sizing from the fabric surface, ensuring a clean and smooth surface. S2, Activation Treatment: The fabric obtained in step S1 is immersed in a pretreatment solution containing 10 g / L of epoxy silane coupling agent and 10 g / L of caustic soda, and treated at 60°C for 30 min, with one immersion and one padding, and a padding rate of 70%. Preparation of finishing solution: 20 g / L flexible acrylic emulsion, 80 g / L 2D resin, 20 g / L crosslinking agent, 55 g / L scouring agent, and 40 g / L softener; S3. Padding Finishing: The fabric obtained in step S2 is placed in the finishing solution prepared above, and then dipped and padded once, with a padded rate of 70%. S4. Pre-baking: Pre-baking at 85℃ for 3 minutes, baking at 115℃ for 2 minutes; S5. Washing and shaping: Wash thoroughly with 45℃ warm water to remove residual additives, and dry and shape at 100℃ to obtain the finished product.
[0028] Example 2 A processing method for improving the pilling resistance of aramid-viscose blended fabrics includes the following steps: S1. Fabric pretreatment: Select an aramid / viscose blended fabric with a weight of 200 g / m². 2 The process involves desizing, boiling, and shaping in sequence. S2. Activation treatment: The fabric obtained in step S1 is immersed in a pretreatment solution containing 10 g / L of epoxy silane coupling agent and 10 g / L of caustic soda. The pretreatment solution is treated at 60°C for 30 min, with one immersion and one padding, and the padding rate is 68%. Preparation of finishing solution: 20 g / L flexible acrylic emulsion, 80 g / L 2D resin, 20 g / L crosslinking agent, 55 g / L scouring agent JL, 40 g / L softener; S3. Padding Finishing: The fabric obtained in step S2 is placed in the finishing solution prepared above, and then dipped and padded once, with a padded rate of 68%; S4. Pre-baking: Pre-baking at 80℃ for 4 minutes, baking at 110℃ for 3 minutes; S5. Washing and shaping: Wash thoroughly with 45℃ warm water, dry and shape at 100℃ to obtain the finished product.
[0029] Example 3 A processing method for improving the pilling resistance of aramid-viscose blended fabrics includes the following steps: S1. Fabric pretreatment: Select an aramid / viscose blended fabric with a weight of 260g / m². 2 The process involves desizing, boiling, and shaping in sequence. S2. Activation treatment: The fabric obtained in step S1 is immersed in a pretreatment solution containing 5 g / L of epoxy silane coupling agent and 15 g / L of caustic soda. The pretreatment solution is treated at 50°C for 40 min, with one immersion and one padding, and the padding rate is 65%. Preparation of finishing solution: 20 g / L flexible acrylic emulsion, 80 g / L 2D resin, 20 g / L crosslinking agent, 55 g / L scouring agent JL, 40 g / L softener; S3. Padding Finishing: The fabric obtained in step S2 is placed in the finishing solution prepared above, and then dipped and padded once, with a padded rate of 65%; S4. Pre-baking: Pre-baking at 80℃ for 4 minutes, then baking at 120℃ for 1.5 minutes; S5. Washing and shaping: Wash thoroughly with 40℃ warm water, dry and shape at 95℃ to obtain the finished product.
[0030] Example 4 A processing method for improving the pilling resistance of aramid-viscose blended fabrics includes the following steps: S1. Fabric pretreatment: Select aramid / viscose blended fabric with a weight of 180g / m², and perform desizing, scouring and setting treatments in sequence. S2. Activation treatment: The fabric obtained in step S1 is immersed in a pretreatment solution containing 15 g / L of epoxy silane coupling agent and 5 g / L of caustic soda. The pretreatment solution is treated at 70°C for 20 min, with one immersion and one padding, and the padding rate is 75%. Preparation of finishing solution (parts by weight): 15 g / L flexible acrylic emulsion, 90 g / L 2D resin, 15 g / L crosslinking agent, 10 g / L scouring agent JL5, 50 g / L softener; S3. Padding Finishing: The fabric obtained in step S2 is placed in the finishing solution prepared above, and then dipped and padded once, with a padded rate of 75%. S4. Pre-baking: Pre-baking at 90℃ for 2 minutes, then baking at 120℃ for 1.5 minutes; S5. Washing and shaping: Wash thoroughly with 50℃ warm water, dry and shape at 105℃ to obtain the finished product.
[0031] Example 5 A processing method for improving the pilling resistance of aramid-viscose blended fabrics includes the following steps: S1. Fabric pretreatment: Select an aramid / viscose blended fabric with a weight of 240 g / m². 2 The process involves desizing, boiling, and shaping in sequence. S2. Activation treatment: The fabric obtained in step S1 is immersed in a pretreatment solution containing 12 g / L of epoxy silane coupling agent and 8 g / L of caustic soda. The pretreatment solution is treated at 65°C for 25 min, with one immersion and one padding, and the padding rate is 72%. Preparation of finishing solution: 25 g / L flexible acrylic emulsion, 75 g / L 2D resin, 22 g / L crosslinking agent, 18 g / L scouring agent JFC, 45 g / L softener; S3, Padding Finishing: The fabric treated in step S2 is placed in the finishing solution prepared above, and then dipped and padded once, with a padded rate of 72%; S4. Pre-baking: Pre-baking at 88℃ for 2.5 minutes, then baking at 118℃ for 2 minutes; S5. Washing and shaping: Wash thoroughly with 42℃ warm water, dry and shape at 98℃ to obtain the finished product.
[0032] II. Comparative Example Comparative Example 1 The difference from Example 1 is that only S1 desizing, boiling and shaping treatment was performed, without S2 activation treatment and S3 finishing liquid padding, that is, no anti-pilling treatment was performed, and it served as a blank control group.
[0033] Comparative Example 2 The difference from Example 1 is that the S2 activation treatment process is omitted. The fabric after S1 desizing, scouring and setting does not undergo activation treatment with pretreatment solution and directly enters the S3 padding and finishing process. The remaining steps and process parameters are the same as in Example 1.
[0034] Comparative Example 3 The difference from Example 1 is that the pretreatment solution in the S2 activation process does not contain epoxy silane coupling agent, but only 10g / L of caustic soda. The remaining steps and process parameters are the same as in Example 1.
[0035] Comparative Example 4 The difference from Example 1 is that polyurethane resin (20g / L) is used instead of flexible acrylic emulsion in the S3 finishing solution, while the other components and process parameters are the same as in Example 1.
[0036] Comparative Example 5 The difference from Example 1 is that the baking temperature of S5 is 150°C and the baking time is 2 minutes, while the remaining steps and process parameters are the same as in Example 1.
[0037] Comparative Example 6 The difference from Example 1 is that no 2D resin is added to the S3 finishing solution, while the remaining components and process parameters are the same as in Example 1.
[0038] Comparative Example 7 The difference from Example 1 is that the crosslinking agent S is replaced with an equal amount of conventional melamine-formaldehyde resin in the S3 finishing solution, while the remaining components and process parameters are the same as in Example 1.
[0039] Comparative Example 8 The difference from Example 1 is that the scouring agent JFC is replaced with an equal amount of sulfosuccinate penetrant in the S3 finishing solution, while the remaining components and process parameters are the same as in Example 1.
[0040] III. Test Examples 1. The anti-pilling grade of the fabric is tested according to GB / T 4802.1-2008 "Textiles - Pilling Test - Circular Locus Method"; 2. Test the air permeability of the fabric according to GB / T 5453-2025 "Textiles - Determination of Air Permeability of Fabrics"; 3. Test the breaking strength of the fabric in accordance with GB / T 3923.1-2013 "Textiles - Tensile Properties of Fabrics - Part 1: Determination of Breaking Strength and Elongation at Break (Strip Method)"; 4. The hand feel was tested in accordance with GB / T 22849-2014 "Subjective Evaluation of Hand Feel and Fabric Style of Textiles".
[0041] The performance tests of the treated fabrics in Examples 1-5 and Comparative Examples 1-8 of this invention are shown in Table 1.
[0042] Table 1. Performance tests of the treated fabrics of Examples 1-5 and Comparative Examples 1-8 of the present invention.
[0043] Although the present invention has been described in detail by way of preferred embodiments, the present invention is not limited thereto. Various equivalent modifications or substitutions can be made to the embodiments of the present invention by those skilled in the art without departing from the spirit and essence of the invention, and such modifications or substitutions should all be within the scope of the present invention. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should also be covered within the protection scope of the present invention.
Claims
1. A processing method for improving the pilling resistance of aramid-viscose blended fabrics, characterized in that, Includes the following steps: S1. The aramid-viscose blended fabric is subjected to desizing, scouring and setting treatments in sequence. S2. Impregnate the fabric with the pretreatment solution obtained in step S1; S3. Apply the fabric padding finishing solution obtained in step S2; S4. The fabric obtained in step S3 is pre-dried and then baked at low temperature in sequence. S5. Wash, dry and set the fabric obtained in step S4 to obtain the finished product.
2. The processing method as described in claim 1, characterized in that, In step S1, the basis weight of the aramid-viscose blended fabric is 180–260 g / m². 2 The mass ratio of aramid fiber to adhesive fiber in the aramid-viscose blended fabric is 30:70 to 70:
30.
3. The processing method as described in claim 1, characterized in that, In step S2, the pretreatment solution includes an epoxy silane coupling agent and caustic soda, wherein the concentration of the epoxy silane coupling agent is 5-15 g / L and the concentration of the caustic soda is 5-15 g / L.
4. The processing method as described in claim 1, characterized in that, In step S3, the finishing liquid comprises the following components in mass concentrations: 15-25 g / L of flexible acrylic emulsion, 75-90 g / L of 2D resin, 15-22 g / L of crosslinking agent, 5-18 g / L of scouring agent, and 40-50 g / L of softener.
5. The processing method as described in claim 4, characterized in that, The flexible acrylic emulsion is an anionic acrylic emulsion, model Appretan® N96101 liq.
6. The processing method as described in claim 4, characterized in that, The 2D resin is mainly composed of a resin condensate with a polyhydroxymethyl structure, model PM-300; the crosslinking agent is model crosslinking agent S; the scouring agent is model scouring HF-JL5; and the softener is model HF-08R.
7. The processing method as described in claim 1, characterized in that, The immersion rolling process adopts a one-immersion-one-roll method, with a roll residue rate of 65% to 75%.
8. The processing method as described in claim 1, characterized in that, In step S4, the pre-drying temperature is 80-90℃ and the pre-drying time is 2-4 min; the low-temperature baking temperature is 110-120℃ and the low-temperature baking time is 1.5-3 min.
9. The processing method as described in claim 1, characterized in that, In step S5, the water washing is done with warm water at 40-50℃, and the drying temperature is 95-105℃.
10. The processing method as described in claim 1, characterized in that, In step S5, the anti-pilling grade of the finished aramid viscose fabric reaches level 4-5, and the anti-pilling grade is not lower than level 4 after 10 washes.
Citation Information
Patent Citations
Methods to improve the anti-pilling and anti-fuzzing properties of acrylic fabrics
CN102433746B
Textile durable wrinkle-resistant, moisture-absorbing, quick-drying and pilling-resistant finishing liquid and finishing method
CN109610173A
Finishing method for improving anti-fuzzing and anti-pilling performance of cotton fabric at normal temperature
CN121538837A
Polyester-mullite blended fabric, method for improving fuzzing and pilling of polyester-mullite blended fabric and application of polyester-mullite blended fabric
CN122257234A